A Scalable Discrete-Time Integrated CMOS Readout Array for Nanopore Based DNA Sequencing - Yunus Dawji (IEEE, 2021)
This paper introduces a high-speed mixed-signal readout array in 130-nm CMOS for the amplification and digitization of picoampere-range signals. Its design is inspired by the needs of emerging DNA sequencing technologies based on biological nanopore sensors. To overcome switching and substrate noise this system adopts an in-pixel analog-to-digital converter (ADC) architecture and a novel readout technique while consuming 10x less power than similar designs described in the literature. The in-pixel ADC architecture is inherently scalable and immune to electrical interference which can be extended to 100s of channels. With a 5 pF input capacitance, the amplifiers achieve a maximum bandwidth of 100 kHz and demonstrate a noise floor as low as 4 fA/ $\sqrt {\text{Hz}}$ and a gain in the range of $\text{G}Ω $ at 10 kHz. Circuit noise behaviour and theoretical maximum performance estimates using behavioural models are also discussed.